Automated optimized parameters for T-distributed stochastic neighbor embedding improve visualization and analysis of large datasets - Anna C. Belkina; Christopher O. Ciccolella; Rina Anno; Richard Halpert; Josef Spidlen; Jennifer E. Snyder-Cappione (Nature Communications, 2019)
Visualisation tools that use dimensionality reduction, such as t-SNE, provide poor visualisation on large data sets of millions of observations. Here the authors present opt-SNE, that automatically finds data set-tailored parameters for t-SNE to optimise visualisation and improve analysis.